A phase II clinical study to assess the feasibility of self and partner anal examinations to detect anal canal abnormalities including anal cancer. (23rd August 2017) - Nyitray, Alan G; Hicks, Joseph T; Hwang, Lu-Yu; Baraniuk, Sarah; White, Margaret; Millas, Stefanos; Onwuka, Nkechi; Zhang, Xiaotao; Brown, Eric L; Ross, Michael W; Chiao, Elizabeth Y
Abstract : Objective: Anal cancer is a common cancer among men who have sex with men (MSM); however, there is no standard screening protocol for anal cancer. We conducted a phase II clinical trial to assess the feasibility of teaching MSM to recognise palpable masses in the anal canal which is a common sign of anal cancer in men. Methods: A clinician skilled in performing digital anorectal examinations (DARE) used a pelvic manikin to train 200 MSM, aged 27–78 years, how to do a self-anal examination (SAE) for singles or a partner anal examination (PAE) for couples. The clinician then performed a DARE without immediately disclosing results, after which the man or couple performed an SAE or PAE, respectively. Percentage agreement with the clinician DARE in addition to sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated for the SAE, PAE and overall. Results: Men had a median age of 52 years, 42.5% were African American and 60.5% were HIV positive. DARE detected abnormalities in 12 men while the men's SAE/PAEs detected 9 of these. A total of 93.0% of men classified the health of their anal canal correctly (95% CI 89.5 to 96.5). Overall percentage agreement, sensitivity and specificity were 93.0%, 75.0% and 94.2%, respectively, while PPV and NPV were 45.0% and 98.3%, respectively. The six men who detected the abnormality had nodules/masses ≥3 mm in size. More than half of men (60.5%) reported never checking their anus for an abnormality; however, after performing an SAE/PAE, 93.0% said they would repeat it in the future. Conclusion: These results suggest that tumours of ≥3 mm may be detectable by self or partner palpation among MSM and encourage further investigation given literature suggesting a high cure rate for anal cancer tumours ≤10 mm.